Handheld Electrocardiogram Design - Huda, Fathul; Guruh irianto, Bambang; A. T. P, Moch. Prastawa (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2021)
Monitoring of ECG signals is very important to help diagnose the situation of a person, especially monitoring body conditions that can be done alone and comfort in patients. To provide comfort and convenience to patients, a portable ECG device with a tapping directly on the finger is needed. The purpose of this study is to monitor the electrocardiogram signal and the BPM value can be done personally by using two leads equipped with a display on the TFT LCD. The contribution of this research is ECG tapping which can be done using the 2 electrode tapping method. So that monitoring of heart conditions can be done easily, providing comfort, does not interfere with movement, and is done alone, this study was designed in a portable manner and uses a tapping of 2 electrodes attached to the finger. Heart signals are obtained from tapping using a series of instrumentation using 2 leads. Furthermore, the signal obtained is filtered and processed to be displayed on a TFT LCD. At the time of data collection, the signal and BPM values are not stable. The results of this study indicate the signal and BPM values are less stable due to the use of filters that have not been right. In this study, ECG monitoring can be implemented easily and can be done alone.